Natural acetylcholinesterase inhibitors: A multi-targeted therapeutic potential in Alzheimer's disease - Kumar Gajendra; G.K. Pratap; D.V. Poornima; Manjula Shantaram; G. Ranjita (Elsevier, 2024)
Alzheimer's disease (AD), the main dementia type accounting for over 70 % of the entire dementia population and exhibits progressive decline in memory and executive function. AD pathology is characterized by amyloid fibrils and neurofibrillary tangles. Acetylcholinesterase (AChE), an enzyme involved in the hydrolysis of the neurotransmitter acetylcholine, consistently colocalizes with the amyloid deposits is characteristic of Alzheimer's disease and may contribute to the generation of amyloid proteins. AChE is a potent amyloid-promoting factor as compared with other associated proteins. AChE inhibitors play a vital role to prevent the formation of toxic oligomeric form of amyloid peptide. Recent studies have reported that acetylcholinesterase inhibitors (ChE-Is) are present in plants, fungi, and marine products. Some cholinesterase inhibitors, obtained from plant source such as rivastigmine, donepezil, and galantamine, used in the treatment of AD, offer an alternative approach to alleviate its symptoms by reducing Aβ.Due to limited efficacy of currently available drugs for AD, there is huge potential of phytomedicines for the treatment of AD. Medicinal herbs and herbal drug preparations have traditionally been used to treat neurological disorders such as AD by exhibiting its anti-inflammatory and neuroprotective properties. Phytomedicines containing flavonoids, polyphenols, and other naturally occurring antioxidants crosses the blood-brain barrier and protect neurons from oxidative stress. As compared to synthetic drugs, phytomedicines have fewer side effects. Therefore, recent research is focused to explore the potential of phytomedicines and develop it as effective treatment for AD. In our review, we summarized the pathology of AD, amyloid-deposition, role of Acetylcholinesterase, potential of phytoconstituents with acetylcholinesterase inhibitory activity for AD treatment.